Kiat Membangun Integritas Mahasiswa Kristen di Era Digital Berdasarkan Teladan Daniel - Efi Nurwindayani; Lavandya Permata Kusuma Wardhani (Sekolah Tinggi Teologi Anugrah Indonesia, 2023)
Today's Christian students are in the digital era which is full of integrity challenges. This research wants to describe how to build the integrity of Christian students in the digital era based on the example of the character Daniel. The Christian students in question are Christian students in Surakarta. This research is a theological research using descriptive qualitative method. Data were collected by means of hermeneutic studies from the text of the Bible Daniel chapter 1 and literature. The results of this research are tips for building the integrity of Christian students in the digital era, namely following character education through Christian Religious Education courses on campus, associating in a healthy way through Christian Student Fellowship facilities on campus and religious discipline in order to build spirituality. ABSTRAKMahasiswa Kristen saat ini ada di era digital yang sarat dengan tantangan integritas. Penelitian ini hendak mendeskripsikan kiat membangun integritas mahasiswa Kristen di era digital berdasarkan teladan tokoh Daniel. Mahasiswa Kristen yang dimaksud adalah mahasiswa yang Kristen yang ada di Surakarta. Penelitian ini adalah penelitian teologis dengan menggunakan metode kualitatif deskriptif. Data dikumpulkan dengan studi hermeneutik dari teks Alkitab Daniel pasal 1 dan literatur kepustakaan. Hasil penelitian ini adalah kiat membangun integritas mahasiswa Kristen di era digital adalah mengikuiti pendidikan karakter melalui mata kuliah Pendidikan Agama Kristen yang ada di kampus, bergaul secara sehat melalui sarana Persekutuan Mahasiswa Kristen di kampus dan disiplin beribadah dalam rangka membangun spiritualitas. Kata-kata kunci: integritas; mahasiswa Kristen; era digital